2011
DOI: 10.1186/1476-7120-9-43
|View full text |Cite
|
Sign up to set email alerts
|

The effect of endogenously released glucose, insulin, glucagon-like peptide 1, ghrelin on cardiac output, heart rate, stroke volume, and blood pressure

Abstract: BackgroundIngestion of a meal increases the blood flow to the gastrointestinal organs and affects the heart rate (HR), blood pressure and cardiac output (CO), although the mechanisms are not known. The aim of this study was to evaluate the effect of endogenously released glucose, insulin, glucagon-like peptide 1 (GLP-1), ghrelin on CO, HR, stroke volume (SV), and blood pressure.MethodsEleven healthy men and twelve healthy women ((mean ± SEM) aged: 26 ± 0.2 y; body mass index: 21.8 ± 0.1 kg/m2)) were included i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 54 publications
3
13
0
Order By: Relevance
“…Other studies reported an early and short-term rise of isoprene concentration in exhaled breath when cardiac output increased [54,55]. Recent investigations support our finding that changes in blood glucose and insulin concentrations may influence the heart rate, cardiac output, and blood pressure [54,56].…”
Section: Discussionsupporting
confidence: 54%
“…Other studies reported an early and short-term rise of isoprene concentration in exhaled breath when cardiac output increased [54,55]. Recent investigations support our finding that changes in blood glucose and insulin concentrations may influence the heart rate, cardiac output, and blood pressure [54,56].…”
Section: Discussionsupporting
confidence: 54%
“…The food effect remained even after implementation of HR correction methodologies and appeared to be unassociated with direct changes in HR. It is recognized that other physiological changes (eg, possibly autonomic perturbations) take place after a meal and that those specific variables were not accounted for within this analysis . Nevertheless, the model performed well in capturing the QT and has significant implications for QT study assessment following a meal or when a cohort is receiving a medication that influences postprandial glucose concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…The correlation between heart rate and MPI has however been found to be insignificant [1] or weak [17]. Physiological changes in the levels of glucose, insulin, glucagon-like peptide 1 (GLP-1) and ghrelin may also influence the activity of the heart [18]. Moreover, it is known that insulin has positive chronotropic and inotropic effects on the heart [19], and the hormone GLP-1 has been shown to improve left ventricular function [20, 21].…”
Section: Discussionmentioning
confidence: 99%
“…The hormone ghrelin has been shown to increase cardiac output (CO) and stroke volume (SV) [2224]. The ingestion of food has also been shown to decrease the diastolic blood pressure [18]. Considering the changes in hemodynamics with increased cardiac output and altered loading conditions it is not surprising that MPI – and more specifically the isovolumetric contraction and relaxation - changes accordingly.…”
Section: Discussionmentioning
confidence: 99%